PENGARUH KONFLIK PERAN DAN AMBIGUITAS PERAN TERHADAP KINERJA PEGAWAI MELALUI MEDIASI STRES KERJA PADA DINAS KESEHATAN KOTA DENPASAR BALI - I Wayan Murdana Yasa (Jurnal Ekonomi dan Bisnis Jagaditha, 2017)
This study aimed to determine the influence of role conflict and role ambiguity to employee performance through the mediation of work stress on health department Denpasar Bali. The hypothesis of this study were (1) The role conflict has a negative influence and significant to the performance of employees, (2) role conflict has a positive influence on work stress, (3) role ambiguity has a positive influence on work stress, (4 ) role ambiguity has a negative influence and significant to the employee performance, (5) the work stress has a negative and significant influence on the employee performance, (6) the influence of work stress in mediating the influence of role conflict on performance, (7) the influence of work stress in mediating influence of role ambiguity on performance. The study design was quantitative, with sample 82 people with census method; the data used were primary data and secondary data, both qualitative and quantitative. With SEM analysis based PLS results of this study were (1) the role conflict has a negative influence and significant on the employee performance, (2) conflicts role has a positive influence and not significant to the work stress, (3) ambiguity role has a positive influence and not significant on the work stress, ( 4) ambiguity role has a positive influence and not significant on the performance of employees, (5) work stress has a positive influence and significant on the performance, while work stress has no influence as the variable that mediate the correlation between role conflict and role ambiguity on employee performance. Suggestions that could be given the leader should strive to give attention to the role that was given to each employee. Given role should be in accordance with the scientific background and expertise that they held previously. The certainty role was very influential in improving the performance of employees within an organization. To subsequent researchers were expected to add to the object of study in order to obtain better results of the research.